1936 Ala. Laws 51 - (:unkn) unknown (My University, 1936)
No. 82, § 8: Prohibited committing a crime of violence when armed with a pistol. Individuals armed with a pistol while being unlicensed shall be prima facie evidence of intention to commit said crime of violence.Violators fined not more than five hundred dollars, or imprisoned not more than one year, or both. Section 1. DEFINITIONS: “Pistol” as used in this Act, means any firearm with barrel less than twelve inches in length. “Crime of Violence’’ as used in this Act, means any of the following crimes or an attempt to commit any of the same, namely, murder, manslaughter, rape, mayhem, assault with intent to rob, assault with intent to ravish, assault with intent to murder, robbery, burglary, kidnapping, and larceny. “Person” as used in this Act, includes firm, partnership, association or corporation. Section 2. COMMITTING CRIME WHEN ARMED: If any person shall commit or attempt to commit a crime of violence when armed with a pistol, he may in addition to the punishment provided for the crime, be punished also as provided by this Act. Section 3. BEING ARMED PRIMA FACIE EVIDENCE OF INTENT: In the trial of a person for committing or attempting to commit a crime of violence, the fact that he was armed with a pistol and had no license to carry the same shall be prima facie evidence of his intention to commit said crime of violence. Section 4. CERTAIN PERSONS FORBIDDEN TO POSSESS ARMS: No person who has been convicted in this State or elsewhere of a crime of violence, shall own a pistol or have one in his possession or under his control. Section 5. CARRYING PISTOL: No person shall carry a pistol in any vehicle or concealed on or about his person, except in his place of abode or fixed place of business, without a license therefor as hereinafter provided. Section 6. EXCEPTION: The provisions of the preceding section shall not apply to marshals, sheriffs, prison or jail wardens or their deputies, policemen or other law-enforcement officers, or to members of the Army, Navy or Marine Corps of the United States or of the National Guard or Organized Reserves when on duty, or to the regularly enrolled members of any organization duly authorized to purchase or receive such weapons from the United States or from this State, provided such members are at or are going to or from their places of assembly or target practice, or to officers or employees of the United States duly authorized to carry a conceal¬ ed pistol, or to any person engaged in the business of manufacturing, repairing, or dealing in firearms or the agent or representative of any such person having in his possession, using, or carrying a pistol in the usual or ordinary course of such business, or to any person while carrying a pistol unloaded and in a secure wrapper from the place of purchase to his home or place of business or to a place of repair or back to his home or place of business or in moving from one place of abode or business to another. Section 7. ISSUE OF LICENSES TO CARRY: The probate Judge, the Chief of Police of a municipality, the Sheriff of a County, may upon the application of any person issue a license to such person to carry a pistol in a vehicle or concealed on or about his person within this State for not more than one year from date of issue, if it appears that the applicant has good reason to fear an injury to his person or property, or has any other proper reason for carrying a pistol, and that he is a suitable person to be so licensed. The license shall be in triplicate, in form to be prescribed by the Secretary of State, and shall bear the name, address, de¬ scription, and signature of the licensee and the reason given for desiring a license. The original thereof shall be delivered to the licensee, the duplicate shall within seven days be sent by registered mail to the Secretary of State and the triplicate shall be preserved for six years, by the authority issuing said license. The fee for issuing such license shall be 50c (fifty cents) which fee shall be paid into the State Treasury. Section 8. DELIVERY TO MINORS AND OTHERS FORBIDDEN. No person shall deliver a pistol to any person under the age of eighteen or to one who he has reasonable cause to believe has been convicted of a crime of violence, or is a drug addict, and habitual drunkard, or of unsound mind. Section 9. SALES REGULATED: No seller shall deliver a pistol to the purchaser thereof until forty-eight hours shall have elapsed from the time of the application for the purchase thereof, and, when delivered, said pistol shall be securely wrapped and shall be unloaded. At the time of applying for the purchase of a pistol the purchaser shall sign in triplicate and deliver to the seller a statement containing his full name, address, occupation, color, place of birth, the date and hour of application, the caliber, make, model, and manufacturer’s number of the pistol to be purchased and a statement that he has never been convicted in this State or elsewhere of a crime of violence. The seller shall within six hours after such application, sign and attach his address and forward by registered mail one copy of such statement to the chief of police of the municipality or the sheriff of the county of which the seller is a resident; the duplicate duly signed by the seller shall within seven days be sent by him with his address to the Secretary of State; the triplicate he shall retain for six years. This section shall not apply to sales at wholesale. Section 10. DEALERS TO BE LICENSED: No retail dealer shall sell or otherwise transfer, or expose for sale or transfer, or have in his possession with intent to sell, or otherwise transfer, any pistol without being licensed as hereinafter provided. Section 11. DEALER’S LICENSES, BY WHOM GRANTED AND CONDITIONS THEREOF: The duly constituted licensing authorities of any city, town, or political subdivision of this State may grant licenses in forms prescribed by the Secretary of State, effective for not more than one year from date of issue, permitting the licensee to sell pistols at retail within this State subject to the following conditions in addition to those specified in Section 9 hereof, for breach of any of which the license shall be forfeited and the licensee subject to punishment as provided in this Act. 1. The business shall be carried on only in the building designated in the license. 2. The license or a copy thereof, certified by the issuing authority, shall be displayed on the premises where it can easily be read. 3. No pistol shall be sold (a) in violation of any provision of this Act, nor (b) shall a pistol be sold under any circumstances unless the purchaser is personally known to the seller or shall present clear evidence of his identity. 4. A true record in triplicate shall be made of every pistol sold, in a book kept for the purpose, the form of which may be prescribed by the Secretary of State and shall be personally signed by the purchaser and by the person effecting the sale, each in the presence of the other, and shall contain the date of sale, the caliber, make, model and manufacturer’s number of the weapon, the name, address, occupation, color and place of birth of purchaser and a statement signed by the purchaser that he has never been convicted in this State or elsewhere of a crime of violence. One copy shall within six hours be sent by registered mail to the chief of police of the municipality or the sheriff of the county of which the dealer is a resident; the duplicate the dealer shall within seven days send to the Secretary of State; the triplicate the dealer shall retain for six years. 5. No pistol or imitation thereof or placard advertising the sale thereof shall be displayed in any part of any premises where it can readily be seen from the outside. The fee for issuing said license shall be 50c (fifty cents) which fee shall be paid into the State Treasury. Section 12. CERTAIN TRANSFERS FORBIDDEN: No person shall make any loan secured by a mortgage, deposit, or pledge of a pistol contrary to this Act, nor shall any person lend or give a pistol to another or otherwise deliver a pistol contrary to the provisions of this Act. Section 13. FALSE INFORMATION FORBIDDEN: No person shall, in purchasing or otherwise securing delivery of a pistol or in applying for a license to carry the same, give false information or offer false evidence of his identity. Section 14. ALTERATION OF IDENTIFYING MARKS PROHIBITED: No person shall change, alter, remove, or obliterate the name of the maker, model, manufacturers number, or other mark of identification of any pistol. Possession of any pistol upon which any such mark shall have been changed, altered, removed, or obliterated, shall be prima facie evidence that the possessor has changed, altered, removed or obliterated the same. Section 15. EXISTING LICENSES REVOKED: All licenses heretofore issued within this State permitting the carrying of pistols concealed upon the person shall expire at midnight of the 1st day of October, 1936. Section 16. EXCEPTIONS: This Act shall not apply to antique pistols unsuitable for use as firearms and possessed as curiosities or ornaments. Section 17. PENALTIES: Any violation of any provision of this Act constitutes an offense punishable by a fine of not more than $500.00 (five hundred dollars) or imprisonment for not more than one year, or both. Section 18. CONSTITUTIONALITY: If any part of this Act is for any reason declared void, such invalidity shall not affect the validity of the remaining portions of this Act. Section 19. SHORT TITLE: This Act may be cited as the "Uniform Firearms Act." Section 20. It is hereby declared to be the Legislative intention in the passage of this Act to further aid in the suppression of crime and the Act is to be liberally construed to effectuate this purpose. Section 21. EFFECTIVE DATE: This Act shall take effect on the 1st day of October, 1936. Section 22. CERTAIN ACTS REPEALED: This Act is intended as an entire revision of the subject matter contained herein and all laws or parts of laws inconsistent herewith are hereby repealed.
Keywords: CARRY - INTENT TO COMMIT CRIME